2019
DOI: 10.3991/ijet.v14i05.9512
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Academic Achievement in Blended Learning: the Case of Data Science Minor

Abstract: This paper is dedicated to studying patterns of learning behavior in connection with educational achievement in multi-year undergraduate Data Science minor specialization for non-STEM students. We focus on analyzing predictors of aca-demic achievement in blended learning taking into account factors related to initial mathematics knowledge, specific traits of educational programs, online and of-fline learning engagement, and connections with peers. Robust Linear Regression and non-parametric statistical tests r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…For this reason, the term of STEM education should be taken with caution, since for some authors it is represented as a pedagogical action that prepares students for university engineering courses; others value it as a career path for an engineering profession, while others value it as a component of general education, when trying to improve STEM knowledge in the population [21]. The use of STEM in education involves students working as a team, to focus on problem solving, to increase decision making and creativity, to improve critical thinking and self-esteem, to acquire significant learning, to develop interaction between peers, to enhance self-efficacy, scientific identity and an attitude towards mathematics and science, to develop active learning, to improve reasoning skills, collaboration and the self-regulation of learning [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, the term of STEM education should be taken with caution, since for some authors it is represented as a pedagogical action that prepares students for university engineering courses; others value it as a career path for an engineering profession, while others value it as a component of general education, when trying to improve STEM knowledge in the population [21]. The use of STEM in education involves students working as a team, to focus on problem solving, to increase decision making and creativity, to improve critical thinking and self-esteem, to acquire significant learning, to develop interaction between peers, to enhance self-efficacy, scientific identity and an attitude towards mathematics and science, to develop active learning, to improve reasoning skills, collaboration and the self-regulation of learning [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…Wang, 2021;Wu et al, 2021), followed by 12 articles published in 2022 (Brunetto et al, 2022;Cavanaugh et al, 2022;DeCoito & Estaiteyeh, 2022;Durandt et al, 2022;Ní Fhloinn & Fitzmaurice, 2022;Gehrtz et al, 2022;Giberti et al, 2022;Kier & Johnson, 2022;Kurianski et al, 2022;Rocha et al, 2022;Segerby, 2022;P. Wang, 2022), 5 articles in 2020 (Bakar, Mohamad & Ismail, 2020;Jeong et al, 2020;Panisoara et al, 2020;Singh-Pillay & Naidoo, 2020;Van Nuland et al, 2020), 4 articles in 2018 (Chen & Huang, 2018;Golding & Bretscher, 2018;Lambert & Alony, 2018;Muirhead et al, 2018) and finally 2 articles have been published in 2019 (Musabirov et al, 2019;Trenholm et al, 2019). The year with the highest number of published articles was 2021.…”
Section: To Identify the Trends In The Implementation Of Hybrid Teach...mentioning
confidence: 99%
“…In general, research approaches can be divided into two, namely quantitative and qualitative. Based on Figure 3 shows the research approach that can be analyzed from 41 articles in this study where the highest is using a qualitative research approach of 19 articles (Ashraf et al, 2021;Bakar et al, 2020;Batra et al, 2021;Bouck & Long, 2021;Brunetto et al, 2022;Church et al, 2021;Ní Fhloinn & Fitzmaurice, 2022;Gehrtz et al, 2022;Golding & Bretscher, 2018;Goulart et al, 2021;Kier & Johnson, 2022;Kurianski et al, 2022;Lambert & Alony, 2018;Muirhead et al, 2018;Pourdavood & Song, 2021;Singh-Pillay & Naidoo, 2020;Trenholm et al, 2019;Nuland et al, 2020;Wang et al, 2020), 16 articles use a quantitative research approach (Aristika et al, 2021;Cao et al, 2021;Cavanaugh et al, 2022;Chen & Huang, 2018;Durandt et al, 2022;Fujita et al, 2021;Giberti et al, 2022;Jeong et al, 2020;Musabirov et al, 2019;Nair & Nair, 2021;Panisoara et al, 2020;Pavlysh et al, 2021;Pócsová et al, 2021;Rasheed et al, 2021;P. Wang, 2022;Wu et al, 2021) and 6 articles using a mixed method research approach (DeCoito & Estaiteyeh, 2022;…”
Section: To Identify the Trend Of Implementing Hybrid Teaching And Le...mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a study carried out in USA among 80000 students showed 27 % fail rate [7]. Mathematics is considered as complex [8,3,9] and as such it is important to investigate reasons and factors that explain this variability in learning mathematics. In social sciences variable or a factor is any entity that can change.…”
Section: Literature Reviewmentioning
confidence: 99%